Analyzing changes in parkinsonian speech over time: a diachronic experimental phonetics study - Pettorino, Massimo; Maffia, Marta (Frontiers in Aging Neuroscience, 2024)
In this contribution the use of web resources for the longitudinal study of speech rhythm of a ‘well-known’ person diagnosed with Parkinson’s disease, the American actor Alan Alda, is proposed. A corpus of 20 speech samples produced in the period between 1979 and 2021 was collected from the web. A rhythmical analysis was conducted, based on two parameters: the percentage of vocalic portion on the total duration of the utterance (%V) and the VtoV, the mean duration of the interval between two consecutive vowel onset points. The results of this study confirm an early alteration of rhythm in parkinsonian speech, with an abnormal increase of %V, already occurring some years before the clinical diagnosis. The observation of speech rhythm variation can therefore be considered as the basis for the realization of a sustainable and non-invasive procedure in support to early diagnosis of Parkinson’s disease.